Establishment and operation of a pilot in vitro active genebank: Report of a CIAT-IBPGR collaborative project using cassava (Manihot esculenta Crantz) as a model - International Center for Tropical Agriculture; International Plant Genetic Resources Institute (1995)
The need to explore various practical and biological aspects of managing an in vitro genebank was identified by the IBPGR Advisory Committee on in vitro storage. In vitro techniques were recognized to hold great promise for the genetic conservation of problem crops that could not be stored as seed. This report will provide unique insights into the complexities of managing an in vitro genebank for cassava and will, undoubtedly, provide an extremely useful baseline to capitalize upon that experience in the management of collections of other crops.